PUCHEU, Alberto. Giorgio Agamben: Poesia, filosofia, crítica. Rio de Janeiro: Beco do Azougue, 2010. 168, p. - Borralho, José Henrique de Paula (Outros Tempos: Pesquisa em Foco - História, 2011)
Boa leitura !